Effects of delay fading and signals on self‐control choices by children. Issue 2 (14th March 2018) - Vessells, Julia; Sy, Jolene R.; Wilson, Alyssa; Green, Leonard
Abstract : The current study is a systematic replication and extension of work by Schweitzer & Sulzer‐Azaroff (1988). The effects of delay fading alone and in combination with signals on choices between larger, delayed reinforcers and smaller, immediate reinforcers by four children with language deficits were examined. For one of the two children exposed to delay fading alone, larger reinforcers were selected at longer delays relative to the initial self‐control assessment. For all four children, the delay‐fading‐plus‐signal condition resulted in selection of larger reinforcers at considerably longer delays relative to the self‐control assessment.